2020
DOI: 10.18196/pt.2020.114.54-62
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Potato Based on Random Amplified Polymorphic DNA and Simple Sequence Repeat Marker

Abstract: The decline in the potato production also occurred in Central Java, which is one of the potato production centers in Indonesia. Data from the Indonesian Ministry of Agriculture ( 2017) stated that the number of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The characteristics of a plant can be demonstrated using an analysis of genetic diversity through morphological and molecular approaches. Both approaches use markers to demonstrate the characteristics of a plant [25]. Morphological characterization is the starting point in the description and classification of germplasm.…”
Section: B Vegetative Characters Of Kepel In the Palace Of Yogyakartamentioning
confidence: 99%
“…The characteristics of a plant can be demonstrated using an analysis of genetic diversity through morphological and molecular approaches. Both approaches use markers to demonstrate the characteristics of a plant [25]. Morphological characterization is the starting point in the description and classification of germplasm.…”
Section: B Vegetative Characters Of Kepel In the Palace Of Yogyakartamentioning
confidence: 99%
“…SSR markers can efficiently facilitate the establishment of genetic linkages due to their high polymorphism level, codominant inheritance, high allele diversity level, randomly wide distribution in the genome, multi-allele, and experimentally reproducible and transferable among related species [9], [10]. Some molecular markers have been applied to the genetic diversity study on potatoes in Indonesia [5], [11]- [15], but only few reported with SSR markers. Therefore, this present study was aimed to quantify the genetic diversity among 29 elite potato varieties in Indonesia and 4 clones that originated from the United States using the 12 SSR markers and to identify the potential genotypes for potato breeding programs.…”
Section: Introductionmentioning
confidence: 99%